Manifold Routes to a Nucleus - Hendrickson, Heather L.; Poole, Anthony M. (Frontiers in Microbiology, 2018)
It is widely assumed that there is a clear distinction between eukaryotes, with cell nuclei, and prokaryotes, which lack nuclei. This suggests the evolution of nuclear compartmentation is a singular event. However, emerging knowledge of the diversity of bacterial internal cell structures suggests the picture may not be as black-and-white as previously thought. For instance, some members of the bacterial PVC superphylum appear to have nucleus-like compartmentation, where transcription and translation are physically separated, and some jumbophages have recently been shown to create nucleus-like structures within their Pseudomonad hosts. Moreover, there is also tantalising metagenomic identification of new Archaea that carry homologues of genes associated with internal cell membrane structure in eukaryotes. All these cases invite comparison with eukaryote cell biology. While the bacterial cases of genetic compartmentation are likely convergent, and thus viewed by many as not germane to the question of eukaryote origins, we argue here that, in addressing the broader question of the evolution of compartmentation, other instances are at least as important: they provide us with a point of comparison which is critical for a more general understanding of both the conditions favouring the emergence of intracellular compartmentation of DNA and the evolutionary consequences of such cellular architecture. Finally, we consider three classes of explanation for the emergence of compartmentation: physical protection, crosstalk avoidance and nonadaptive origins.